DECODING THE DOMESTIC PRISON: A SEMIOTIC ANALYSIS OF EVERYDAY OBJECTS IN GILMAN'S 'THE YELLOW WALLPAPER - Rizki Fauzi; Ahmad Rizal Abdullah (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study explores the hidden mechanisms of patriarchal oppression in Charlotte Perkins Gilman’s short story, The Yellow Wallpaper. While previous studies have widely discussed its general feminist themes, there is a lack of research analyzing how specific everyday objects actively build this oppressive atmosphere. To fill this gap, this study applies Roland Barthes’ three-level semiotic theory—denotation, connotation, and myth—to decode ordinary household items within the story. Using a qualitative approach based on document analysis and close reading, the textual data was analyzed using the interactive model by Miles, Huberman, and Saldaña. The findings reveal that the husband's medical authority, the barred nursery room, and the ugly yellow wallpaper work together as a complex sign system. This system is carefully designed to normalize male dominance, treat the adult female protagonist like a helpless child, and silence her intellectual freedom. Ultimately, this semiotic analysis uncovers a tragic myth: the patriarchal system would rather drive a woman completely insane than grant her true equality. This study concludes that ordinary objects in literature are not just simple backgrounds, but powerful tools that carry deep ideological meanings about gender and systemic control.